Apical periodontitis promotes insulin resistance and alters adaptive immunity markers in rats - Renato Felipe Pereira; Gestter Willian Lattari Tessarin; Fernando Yamamoto Chiba; Maria Sara de Lima Coutinho Mattera; Amanda Gomes Pereira; Thais Verônica Saori Tsosura; Victor Gustavo Balera Brito; Renan Akira Fujii de Oliveira; Edilson Ervolino; Sandra Helena Penha de Oliveira; Luciano Tavares Angelo Cintra; Doris Hissako Matsushita (Saudi Dental Journal, 2021)
Objective: Apical periodontitis (AP) is a chronic or acute inflammatory disease usually developed from endodontic infections, predominantly due to gram-negative anaerobic bacteria invading the dental pulp. This study aimed to evaluate lymphocyte markers to assess the involvement of adaptive immunity in insulin resistance (IR) in a rat model of AP.Design.Forty-five male Wistar albino rats were divided into 3 groups (control, 1AP and 4AP). AP was induced in the upper right first molar (1AP), and in the first and second upper and lower right molars (4AP). The spleen was collected to evaluate the expression of transcription factors involved in lymphocyte polarization, including T-bet (Th1), GATA3 (Th2), and FOXP3 (Treg). Blood samples were assessed for serum cytokine levels transcribed by the respective lymphocyte polarizations, INF-γ (Th1), IL-4 (Th2) and TGF-β (Treg). In addition, glucose and insulin levels were measured to evaluate IR by the HOMA-IR method. Results: The results showed higher T-bet expression on AP groups, along with lower GATA3 and FOXP3 expression in the 1AP, in addition to increased GATA3 and decreased FOXP3 expression in the 4AP group compared to the CN group. There was no difference in the INF-γ levels, while IL-4 was decreased in the AP groups. Taken together, these results suggest that the adaptive immune system, with a predominance of the Th1 polarization, may be involved in the development of IR in rats with AP. Conclusions: AP promotes increase in the expression of T-bet (4AP) and decrease of FOXP3 expressions and IL-4 levels (1AP and 4AP). However, depending on the number of lesions (1 or 4 lesions), the expression of GATA3 appears differently. Thus, innate immunity and adaptive immunity may contribute to the IR observed in rats with AP.